FINANCIAL PERFORMANCE ANALYSIS OF PT. INDORITEL MAKMUR INTERNATIONAL TBK, ON THE INDONESIAN STOCK EXCHANGE Ismah1), Muryani Arsal 2) Nasrullah3) - Ismah, Ismah; Muryani Arsal; Nasrullah, Nasrullah (CV. AFDIFAL MAJU BERKAH, 2024)
The aim of this research is to determine the comparison of financial performance as measured through financial ratio analysis, which consists of: Liquidity Ratios With Indicators Current Ratio, Cash Ratio,Working Capital To Asstes, Solvency Ratios With Indicators Debt Ratio,Debt Ratio, Debt To Equity Ratio, Activity Ratios With Indicators Total Asset Turnover, Receivable Turnover, Working Capital Turnover, And Profitability Ratios With Profit Indicators, Margin. Return On Investment, Return On Equity. The objek of research is PT. Indoritel Makmur Internasional Tbk. The type of research carried out is quantitative. The results of this research show the financial performance of PT. Indoritel Makmur Internasional, Tbk on the indonesia stock exchange 2019-2023. The liquidity value decreases, the solvency ratio value decreases, the activity ratio decreases, the profitability ratio is constant. The results of this research can be used by PT. Indoritel Makmur Internasional, Tbk to evaluate financial performance, espacially those experiencing decline.